Blindness and laser photocoagulation in patients with childhood-onset type 1 diabetes in Japan. Issue 6 (11th March 2009) - Sano, H; Nishimura, R; Asao, K; Matsudaira, T; Morimoto, A; Agata, T; Shimizu, H; Tajima, N; ,
Abstract : Aim: The aim of the study was to investigate trends in the incidence of blindness and the association with laser photocoagulation in patients with type 1 diabetes in Japan. Methods: Patients diagnosed between 1965 and 1979 aged under 18 years old were studied. The status of blindness and laser photocoagulation was identified as of 1 January 1995. To examine the time trend, we divided the cohort into two groups: 285 patients diagnosed between 1965 and 1969 (65–69 cohort) and 769 patients diagnosed between 1975 and 1979 (75–79 cohort). Survival analysis was performed using the Kaplan–Meier method. Cox proportional hazard models were used to assess the demographic characteristics. Results: Blindness developed in 60 subjects in the 65–69 cohort and 15 subjects in the 75–79 cohort. The incidence of blindness in the 75–79 cohort was significantly lower than that in the 65–69 cohort (p<0.0001). In spite of no change in the use of laser photocoagulation in the 75–79 cohort compared with the 65–69 cohort, the hazard ratio for the blindness in those who received laser photocoagulation in the 75–79 cohort decreased significantly to 0.55 (p<0.01) compared with those in the 65–69 cohort when adjusted for the age of onset, sex, and time of diagnosis. Conclusion: The incidence of blindness decreased significantly for the subjects diagnosed more recently. The change in quality and the earlier introduction of laser photocoagulation might have contributed to the decreased incidence of blindness observed over time.